2013
DOI: 10.1024/2235-0977/a000040
|View full text |Cite
|
Sign up to set email alerts
|

Das Mathematikangstinterview (MAI): Erste psychometrische Gütekriterien

Abstract: Aktuelle Studienergebnisse verdeutlichen, dass sich Kinder bereits im frühen Grundschulalter hinsichtlich ihrer Mathematikangst unterscheiden und dass diese mit deren Mathematikleistung korreliert (Vukovic et al., 2013;Wu et al., 2012

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
(75 reference statements)
2
9
0
2
Order By: Relevance
“…This is a promising result regarding the widely discussed stereotype that females are expected to be worse in math related topics and that females experience more math anxiety. Our findings are consistent with research indicating that countries providing equal education for females and males show little or no gender differences in mathematical performance (Spelke, 2005 ; Kohn et al, 2013 ). The reason why no gender differences in math anxiety were evident might be due to increasing evidence that such gender differences only develop at adolescence as consequence of societal exposure to gender stereotypes (e.g., Johns et al, 2005 ), or female teachers who experience math anxiety themselves (Beilock et al, 2010 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is a promising result regarding the widely discussed stereotype that females are expected to be worse in math related topics and that females experience more math anxiety. Our findings are consistent with research indicating that countries providing equal education for females and males show little or no gender differences in mathematical performance (Spelke, 2005 ; Kohn et al, 2013 ). The reason why no gender differences in math anxiety were evident might be due to increasing evidence that such gender differences only develop at adolescence as consequence of societal exposure to gender stereotypes (e.g., Johns et al, 2005 ), or female teachers who experience math anxiety themselves (Beilock et al, 2010 ).…”
Section: Discussionsupporting
confidence: 92%
“…Hence, we hypothesized that priming effects could appear when groups were separated by extreme levels of mathematics anxiety. Concretely, this examination included a direct measure of mathematics anxiety (assessed by the MAI Kohn et al, 2013 ). This explicit measure of mathematics anxiety is an interesting add-on to our examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Math anxiety is important in psychological research due to its consequences: avoidance of future mathematics related career ( Ashcraft, 2002 ) and course choices ( Chipman et al, 1992 ) or situations containing mathematics even in daily life context ( Kohn et al, 2013 ). In the PISA 2012 study, overall 59% of students reported worrying that it will be difficult for them in mathematics classes, and 30% feel helpless when doing a mathematics problem ( OECD, 2013 ).…”
Section: Math Anxietymentioning
confidence: 99%
“…Particularly for children with DD a computerized training provides the possibility of a learning environment detached from competitive performance pressure and peer comparisons in the classroom context and offers a less stressful and socially risk-free setting to explore mathematics (Käser and von Aster, 2013). This is especially important, since the repeated experience of failure may lead to math anxiety or negative attitudes toward the subject or the teacher, which in turn may decrease the achievement potential and learning ability (Ashcraft and Faust, 1994;Kohn et al, 2013).…”
Section: Introductionmentioning
confidence: 99%